Predominance of III/ST19 and Ib/ST10 Lineages With High Multidrug Resistance in Fluoroquinolone-Resistant Group B Streptococci Isolates in Which a New Integrative and Conjugative Element Was Identified - Gao, Kankan; Gao, Chunyan; Huang, Lianfen; Guan, Xiaoshan; Ji, Wenjing; Chang, Chien-Yi; McIver, David J.; Deng, Qiulian; Zhong, Huamin; Xie, Yongqiang; Deng, Lei; Gao, Fei; et al. (Frontiers in Microbiology, 2021)
Fluoroquinolone (FQ)-resistant Group B Streptococcus (GBS) has been reported with considerable cross-resistance, worsening the crisis of multidrug-resistant (MDR) GBS in clinical settings. However, national epidemiological data on FQ-resistant GBS in mainland China have not been well-characterized. This study aimed to determine the prevalence of FQ resistance among GBS from neonatal invasive infections and maternal colonization in northern and southern China, to investigate the serotyping, multilocus sequence typing, and antibiotic cross-resistance, and to characterize the mutations in gyrA and parC genes in quinolone resistance-determining region (QRDR). In order to provide a comprehensive view of the location and structure of resistance genes, whole-genome sequencing on III/ST19 MDR isolates were performed. Among 426 GBS, 138 (32.4%) were FQ resistant, with higher prevalence in northern China than in southern China in both neonates (57.8%, 37/64 vs. 21.7%, 39/180) and pregnant women (50.9%, 29/57 vs. 26.4%, 33/125). Serotypes were distributed as III (48.5%), Ib (39.9%), V (6.5%), and Ia (5.1%). Sequence types were mainly ST19 (53.6%) and ST10 (39.1%), followed by ST12 (1.4%), ST17 (1.4%), ST23 (1.4%), and 0.7% each of ST27, ST188, ST197, and ST597. ST19 isolates were more prevalent in southern China than in northern China in both neonates (64.1%, 25/39 vs. 27.0%, 10/37) and pregnant women (81.8%, 27/33 vs. 41.4%, 12/29), whereas ST10 isolates were more common in northern China than in southern China in both neonates (64.9%, 24/37 vs. 20.5%, 8/39) and pregnant women (58.6%, 17/29 vs. 15.2%, 5/33). Serotype III isolates were mainly ST19 (89.6%, 60/67), while Ib isolates were largely ST10 (94.5%, 52/55). Sequencing data revealed several mutations in QRDR, including Ser81Leu in gyrA (99.2%, 130/131), Ser79Phe or Tyr in parC (76.2%, 48/63), and a previously unreported Ile218Thr and Ile219Phe double mutation pattern (49.2%, 31/63) in parC. ST10 isolates were associated with Ser79Phe (84%, 21/25), while ST19 isolates were limited to Ser79Tyr (95.7%, 22/23). A new integrative and conjugative element (ICE) harboring tetM and gyrA genes was identified in a III/ST19 isolate. This study investigates the molecular characteristics of FQ-resistant GBS in northern and southern China, emphasizing the need for continuous surveillance geographically and further research to characterize the mechanisms of ICE transfer.